2015
DOI: 10.1093/molbev/msv146
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Landscapes of Resistance Genes Change as Antibiotic Concentrations Change

Abstract: Most studies on the evolution of antibiotic resistance are focused on selection for resistance at lethal antibiotic concentrations, which has allowed the detection of mutant strains that show strong phenotypic traits. However, solely focusing on lethal concentrations of antibiotics narrowly limits our perspective of antibiotic resistance evolution. New high-resolution competition assays have shown that resistant bacteria are selected at relatively low concentrations of antibiotics. This finding is important be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 25 publications
1
62
1
Order By: Relevance
“…Previous work with antibiotic resistance in bacteria has shown that the shape of fitness landscapes can be strongly dependent on antibiotic concentrations [31]. Interestingly, we found that the negative interactions observed between beneficial mutations at lower concentrations of nystatin reversed sign and became increasingly positive at higher concentrations of nystatin.…”
Section: Introductionmentioning
confidence: 53%
“…Previous work with antibiotic resistance in bacteria has shown that the shape of fitness landscapes can be strongly dependent on antibiotic concentrations [31]. Interestingly, we found that the negative interactions observed between beneficial mutations at lower concentrations of nystatin reversed sign and became increasingly positive at higher concentrations of nystatin.…”
Section: Introductionmentioning
confidence: 53%
“…Another consideration is the potential of the core gene models for identifying compensatory or epistatic changes throughout the genome. These mutations occur in non-AMR genes in order to accommodate the potentially reduced fitness cost of maintaining the primary AMR conferring genes or SNPs [67][68][69][70] . The results of this study, and previous AI studies focusing on AMR 25,27 , suggest that these changes could be widespread throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Following [74], datasets reporting growth rates [4,11,14,16,23,25,77] or drugresistance phenotypes [9,37,42,43,49,73] were log-transformed before analysis. Following [49], negative two was used in place of log-transformed values when growth rate or drug resistance phenotypes of zero were observed.…”
Section: Empirical Datasetsmentioning
confidence: 99%